Hubungan antara berat hidup dan ukuran vital tubuh dengan berat karkas kambing kacang janatan di rumah potong hewan sukun kota malang - Ahmad mawardi; henny leondro; Enike Dwi Kusumawati (Jurnal Sains Peternakan, 2018)
ABSTRACT The purpose of this research was to know carcass weight based on weight cutting, as data information. The hypothesis of this research is carcass weight that can use based on weight cutting. This research uses the case study method, taking a sample as purposive sampling. It is a sample that takes from all of the goats and it collects based on various age, gender. From the research, the average of weight cutting 20,42+4,60, body tall 62,75+2,86, body long 52,29+2,96, chest size 86,38+4,28 and carcass weighty = 9,54+2,74. While the similarity regression between weight cutting carcass weight male kacang goat P1 – P4 = -1,884 + 0,530, similarity regression between body long and carcass weight male kacang goat P1 – P4 y = -29,680 + 0,727, similarity between ches size and carcass weight male kacang goat P1 – P4 y = -33,807 + 0,488. The regression equation above result indicates the inexistence of a positive relationship is highly significant (t>t table 0,01). By looking at the regression equation it can be concluded that the percentage of carcass and weight will be followed by an increase in carcass weight and carcass percentage. Carcass weight and carcass percentage can be estimated based on the weight of intersection, everybody weight recommended that the weighing of livestock, to obtain estimates of carcass weight and percentage by weight of intersection.